Evidence for drought and forest declines during the recent megafaunal extinctions in Madagascar - Virah-Sawmy, M; Willis, K; Gillson, L (2010)
Aim There remains some uncertainty concerning the causes of extinctions of Madagascar's megafauna. One hypothesis is that they were caused by over-hunting by humans. A second hypothesis is that their extinction was caused by both environmental change and hunting. This paper systematically addresses the second hypothesis through examination of two new pollen records from south-eastern Madagascar alongside other published records across the island. Location South-eastern Madagascar. Methods We reconstructed past vegetation and fire dynamics over the past 6000 years at two sites in south-eastern Madagascar (Ste-Luce) using fossil pollen and charcoal contained in sedimentary sequences. We investigated drivers of vegetation changes and how these, in turn, influenced faunal species in the south-east, using published climatic, archaeological and faunal records. Further, we also used published records to provide a synthesis of environmental changes on the whole island. Results Vegetation reconstructions indicate that the mosaic vegetation in the region of Ste-Luce was highly dynamic in response to climatic changes. The open woodland, surrounding the littoral forest, transformed into an ericoid grassland between c. 5800 and 5200 cal. yr bp, possibly in response to a moderate drought recorded during this period. The littoral forest was more stable between c. 5100 and 1000 cal. yr bp, with only some minor compositional changes c. 2800 cal. yr bp and between c. 1900 and 1000 cal. yr bp. Significant forest decline, however, is observed at c. 950 cal. yr bp, coinciding with a drought and a marine surge. A comparison of these results with a synthesis of published vegetation records across the island shows asynchronous vegetation changes in response to various droughts during the Holocene, except for the 950 cal. yr bp drought event, with evidence of widespread vegetation transformations and fires across the island. Main conclusions Pronounced climatic desiccation between 1200 and 700 cal. yr bp may have been the slow driver framing and triggering vegetation transformations and decline in megafaunal populations. In addition, hunting by drought-impacted human inhabitants and competition with newly introduced cattle would have amplified the impacts on megafaunal populations, leading to numerous extinctions in this period. © 2009 Blackwell Publishing Ltd.